Optimization and Evaluation of Authentication System using Blockchain Technology - Imam Riadi; Aulyah Zakilah Ifani; Ridho Surya Kusuma (Emerging Science Journal, 2020)
User data security innovation is a particular concern in protecting one's privacy rights, which is one of the serious violations when an attacker can bypass the user authentication so that it looks like something legitimate and becomes legal. Based on these issues, the research aims at optimizing and evaluating the blockchain-based authentication systems to minimize data leakage, manipulate the data, and modify the data. Blockchain is one of the innovations that can solve this problem. Data or transactions in the blockchain are saved in hash form to make it difficult for hackers to break into them. The Blockchain implementation uses the Solidity programming language to build smart contracts and other tools such as MetaMask, Ganache, and Truffle. The Network Forensics Development Life Cycle (NFLDC) is used as a framework with the following five stages: Initiation, Acquisition, Implementation, Operation, and Disposition. Based on the research conducted, the attack strategy against blockchain-based systems consists of several scenarios covering the Burp Suite, XSS, SQL Injection, and DoS. The results show that the percentage of authentication optimization reaches a value of 90.1%, and 8.9% is the percentage for evaluating systems such as the possibility of cyberattack. Based on these results, this research has achieved its goals and may assist in further research. Doi: 10.28991/esj-2021-SP1-015 Full Text: PDF